Regime of Taxation - Definite Article 14 Ter - Calderón Torres, Pablo; Rojas Peralta, Lisette (Revista de Estudios Tributarios, 2016)
The current article makes a brief analysis of the amendments introduced into the taxation system that affect those accumulated profits pending of taxation that maintain taxpayers forced to determine their actual income according to full accounting and balance sheet and choose incorporating to letter A from the article 14 ter of the LIR. This analysis will be conducted through simple examples, with the aim to clarify the tax effects that will compromise such taxpayers. To this end, firstly, it will be studied the option that taxpayers who want to be incorporated into the simplified regime in the exercise years 2015 and 2016, in order to continue with those who will incorporate from 2017. Finally, a brief analysis will be made to the amendments made by the Law Nº 20.899 of 2016 to the linkage policies in the article 14 ter, letter A), whose effects should be considered at the moment of measuring the income level in order to remain in the simplified regime.